The Effect Of Perineal Massage On Perineal Rupture In Primigravida In The Tamansari Health Centre Area Of Tasikmalaya City - Ericke Dwi Ratnasari; Dita Eka Mardiani; Uly Artha Silalahi (Media Informasi, 2026)
Background: Primigravida women have a high risk of experiencing perineal rupture during childbirth. Perineal rupture can lead to complications such as bleeding and infection. If the care provided is inadequate, this condition can interfere with the mother's activities after giving birth. Perineal massage is one non-pharmacological method that has the potential to reduce the risk of rupture. Objectives: To analyze the effectiveness of perineal massage in reducing the risk of perineal rupture in primigravida women. Methods: The study design used was a quasi-experimental design with a single measurement after intervention. Two groups were involved: the intervention group and the control group. The study was conducted at the Tamansari Health Center in Tasikmalaya City from April to May 2025, using observation sheets and checklists as research instruments. Results: Data analysis was performed using the Mann-Whitney U test. The p-value obtained was 0.00 (p < 0.05), indicating a significant difference between the intervention group and the control group. Conclusion: Pregnant women are encouraged to learn perineal massage techniques so they can be applied during pregnancy to prevent perineal rupture.